New Neolithic sites in the western al‐Hajar mountains. (3rd October 2019) - Białowarczuk, Marcin; Szymczak, Agnieszka
Abstract: A new archaeological project in the western al‐Hajar Mountains in northern Oman involves a systematic survey of the small valley of Qumayrah and excavation of selected sites. Two field seasons revealed a number of Neolithic settlement traces. Three newly discovered sites were excavated, two of which proved to be stratified. The most intensive fieldwork focused on QA 2, a Stone Age campsite that contained stone structures, numerous lithic tools, stone and shell beads and marine shell fragments. Radiocarbon dating provided a c. 4200 cal. BC age, corresponding with the prevalent lithic evidence. Two other excavated sites yielded fewer materials, that were, however, diagnostically relevant. They indicate a diachronic occupation ongoing probably since the Late Neolithic till the end of that period, but some materials point to other stages of the Neolithic period as well. The appearance of marine shells suggests seasonal occupation and connections with coastal areas. It raises questions about the reasons for the settling of the Qumayrah valley.